2011
DOI: 10.1177/0003319711420608
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor and Its Basic Metabolic Enzymes in Blood of Naive HIV-Infected Patients

Abstract: Platelet-activating factor (PAF), a mediator of proatherosclerotic inflammatory processes, is also implicated in endothelial dysfunction during human immunodeficiency virus (HIV) infection. We examined PAF metabolism in blood of naive male patients, 8 with early HIV infection (group A) and 17 just before treatment initiation (group B), versus 18 healthy age-matched males (group C). Statistical analysis was performed with 1-way analysis of variance (ANOVA) criterion and Pearson r test. Higher PAF biosynthesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 43 publications
5
34
0
Order By: Relevance
“…This is in accordance with the study of Klovidhunic et al reporting that suppression of IlIV viremia by either a protease inhibitor or lamivudine was not accompanied by a lower level of LpPLA 2 activity (30). In the present study we found that LpPL~activity was positively correlated with viral load at baseline, an observation that is consistent with our previous reports (9). However, it should also be mentioned that the positive correlation of LpPLA 2 with viral load was diminished in partial correlations after adjusting for several cofounders such as LDL cholesterol which is known to be the main carrier of this enzyme in plasma.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This is in accordance with the study of Klovidhunic et al reporting that suppression of IlIV viremia by either a protease inhibitor or lamivudine was not accompanied by a lower level of LpPLA 2 activity (30). In the present study we found that LpPL~activity was positively correlated with viral load at baseline, an observation that is consistent with our previous reports (9). However, it should also be mentioned that the positive correlation of LpPLA 2 with viral load was diminished in partial correlations after adjusting for several cofounders such as LDL cholesterol which is known to be the main carrier of this enzyme in plasma.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, since PAF downregulates CD4 proliferation (29), it is possible that the negative correlation of Lyso-PAF-AT with CD4 cell counts at baseline reflects an implication of increased PAF levels in HIVinduced immunosuppression. This observation is in accordance with our previous data reporting a negative correlation between Lyso-PAF-AT of HLs and CD4 cell counts (9). However, naive patients differed between our two studies in terms of duration of HIV infection and viral load levels (9).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In mammals for example, the de novo pathway contributes to PAF synthesis for maintaining its basal levels under physiological conditions, while the remodeling pathway is activated under inflammatory situations. However, the de novo pathway, especially PAF-CPT, may contribute to systemic disorders such as cancer (25), central nervous system failure (26), and AIDS (27). As far as we know there has been no previous study to give sufficient data regarding the contribution of these two distinct basic PAF biosynthetic enzymes in any protozoa.…”
Section: Discussionmentioning
confidence: 99%